2021
DOI: 10.3390/horticulturae7120568
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Harvest Application of Salicylic Acid, Abscisic Acid, and Methyl Jasmonate Conserve Bioactive Compounds of Strawberry Fruits during Refrigerated Storage

Abstract: The short shelf-life and loss of bioactive compounds of strawberry fruit are the most important problems during strawberry refrigerated storage. This study was carried out to evaluate the effect of the pre-harvest foliar application of salicylic acid (SA) (2 and 4 mM), abscisic acid (ABA) (0.25 and 0.50 mM), and methyl jasmonate (MeJA) (0.25 and 0.50 mM) three times, 10 d apart, at fruit development and ripening stages on storage ability and bioactive compounds of strawberry fruit (cv. Festival) stored at 4 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Anthocyanin (mg 100 g −1 ) was measured, as described by Darwish et al [19]. Briefly, the samples were extracted with 40 mL of ethanol to quantitatively evaluate anthocyanin content, then centrifuged for 20 min at 6000 rpm.…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…Anthocyanin (mg 100 g −1 ) was measured, as described by Darwish et al [19]. Briefly, the samples were extracted with 40 mL of ethanol to quantitatively evaluate anthocyanin content, then centrifuged for 20 min at 6000 rpm.…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…Therefore, several researchers stated that pre and/or postharvest applications are needed to prolong shelf life and conserve florets' quality and nutritional quality after harvesting (Lai et al, 2011;Han et al, 2022;Elsayed et al, 2022). Various pre and postharvest materials have been used to increase the storability and delay the damage of Brassica floret such as utilization of methyl jasmonate (Darwish et al, 2021), melatonin (Onik et al, 2021), ozone and ultraviolet-C radiation application (Huyskens-Keil et al, 2012), and tapioca-starch edible coating (Owolabi et al, 2021). However, the application of some previous post-harvest treatments couldn't be applicable due to the high cost, low customer acceptance, or difficulty to apply.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Strawberry ( Fragaria x ananassa) is considered one of the most important vegetables belonging to the Rosaceae family. The fruits of strawberries contain important minerals, fibres, vitamins (especially ascorbic acid), and antioxidant compounds such as pigments (anthocyanin), phenolic compounds, and carotenoids [ 1 , 2 ]. Additionally, it has been suggested that daily consumption of strawberries (10–454 g) could reduce the risk of cardiovascular disease and type II diabetes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%